Використання ПЛІС для мереж інтернету речей - Старокожев, С. В. (ХНУРЕ, 2025)
The article examines the use of field-programmable gate arrays (FPGAs) in modern Internet of Things (IoT) networks. Key requirements for such networks are analyzed, including high data throughput, minimization of transmission de lays, and security assurance, as well as how the use of FPGAs helps meet these requirements. While typical IoT solutions are better suited for ASICs or embedded processors, the flexibility and reconfigurability of FPGAs make them essential for projects that require specialized networking solutions and adaptation to unique requirements.
Keywords: використання ПЛІС; інтернет речей